Pengembangan bahan ajar modul limit fungsi untuk meningkatkan kemampuan representasi siswa - Khafidta, Vivi; Muhtarom, Muhtarom; Happy, Nurina (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Teaching material is supporting student learning success. In this study, the researcher developed teaching materials in the form of modules with algebraic function limit material. Module teaching materials of this study was conducted based on the low ability of student representation in the algebraic function limit material. The purposes of this study are (1) to know the module as a worthy / valid teaching material used to improve students 'representation ability in the mathematics learning process on the material limit function, (2) to know the effectiveness of the module as a mathematics teaching material to improve students' representation ability in the mathematics learning process on the functional limit material, (3) to know the practicality of the module as a mathematics teaching material to improve the representation ability of students in the mathematics learning process on the material limit function. This development research model is using the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The population of this study was XI grade students of SMAN 1 Bae Kudus. Pre-experimental research design with one group pretest-posttest design was used as a method in this study. The average value of validation obtained by media experts was 84%, and material experts was 80%. Besides that, the algebra function limit module is declared to be effectively used because of an increase in the average student score, based on the average student's pretest acquisition of 34.33 and the average posttest obtained of 72.33. The result of the N Gain Test also showed that there was an increase in the pretest and posttest result of 0.58 which meant an increase in the moderate category. The function limit module is also practically used based on the acquisition of questionnaire analysis of 97.78%. Based on the research results obtained, it can be concluded that the module teaching material for the algebraic function limit that has been developed is feasible for students to use.